Implementasi Pembelajaran PJOK secara Daring di SMPN 3 Kaliwungu Kabupaten Kendal Tahun 2021 - Lianita Agustina Sari; Mugiyo Hartono (Indonesian Journal for Physical Education and Sport, 2023)
This study aims to determine and analyse the implementation of online learning at SMP Negeri 3 Kaliwungu. The research method used is a qualitative research with a descriptive approach. Collecting data using triangulation methods with observation, interviews and documentation. The instruments used are instrument interviews and documentation. The data analysis model used in this study is SWOT analysis.The results of the study are as follows : Strength : increase the ability of teachers and students in using technology. Weakness : PJOK teachers cannot monitor and evaluate student movements directly. Opportunities : there are students who become more creative. Threats : students feel they do not understand the material given by the PJOK teacher because it is only theory.